Tethered money : managing digital currency transactions - Samid, Gideon, 1945- (Academic Press, 2015)
Tethered Money: Managing Digital Currency Transactions presents a comprehensive discussion of financial transactions using digital currencies, with the author, Gideon Samid, making the case for their expansion in tethered money. Exploring the technical, legal, and historical aspects of digital money, the author discusses how the emerging technology of money specified for a specific need or to perform a particular task will affect society. The ability to dictate, Samid argues, how money is spent could increase control over our lives and resources, enabling us to practice a certain efficiency that would, in due time, become a pillar of civilization. Informative and thought-provoking, the book describes an evolving future that, in some quarters, has already arrived.